Warranty Deed, Camden County, 1864 - State of Georgia, Camden County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1864)
Warranty Deed, Camden County, 1864. Handwritten record. Deed between Francis Readdick and N.B. Stafford. Recorded April 5, 1869. Camden County, Georgia. March 14, 1864. 2 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Camden County (Ga.); Court Records; Records and correspondence